Potential for intramyocardial fibrosis detection based on estimation of extracellular volume using dual-energy computed tomography - E. A. Mershina; D. A. Filatova; M. V. Lisitskaya; E. V. Ryzhkova; R. P. Myasnikov; V. E. Sinitsyn (Столичная издательская компания, 2023)
An increase in left ventricular (LV) extracellular volume (ECV) is an important parameter of LV morphology and is considered synonymous with myocardial fibrosis, as well as a reliable marker of myocardial injury and impaired cardiac function. Accurate methods for detecting and assessing myocardial fibrosis are very important for clinical practice. The current standard for myocardial fibrosis imaging is delayed gadolinium enhanced cardiac magnetic resonance imaging (MRI) or T1 mapping, but these techniques have limitations. They can be avoided by using dual-energy computed tomography (DECT), which makes it possible to identify myocardial fibrosis, including small-focal fibrosis, in two different ways (subtraction technique and iodine density measurement technique). The literature analysis carried out by the authors showed good comparability of MRI and DECT results in determining ECV in patients with various heart diseases of both ischemic and non-ischemic nature, including cardiomyopathies, aortic stenosis, pulmonary hypertension, sarcoidosis, and amyloidosis. In addition, the use of DECT to identify myocardial fibrosis is also possible if cardiac inflammation is suspected. In addition to evaluating the effectiveness of DECT compared with MRI, different scanning protocols were analyzed, since there is currently no consensus on the optimal contrast administration regimen. The issue of radiation exposure in modern DECT scanners is also separately considered. The authors showed that DECT is an important tool for determining ECV, which is of interest for clinical practice.